An overview on wilt disease on acacia mangium plantation in Sabah, Malaysia - N.M. Yunus; M. Sudin; Mandy Maid; W.T.L. Yong; F.E. Anthony (Faculty of Science and Natural Resources, 2020)
As generally typical in other monoculture industries, Acacia mangium plantations are also threatened by the wilt disease symptoms which was observed preliminarily to cause about 50% mortality rate in various establishments in Sabah, Malaysia. The disease resulted from the disturbance of normal physiological function in the vascular system of the plants. On the above-ground, the effects are exemplified by gradual foliar chlorosis, necrosis, defoliation, sapwood discoloration, gummosis, fermented exudate with fruiting odours; whereas for belowground darks streaks in the xylem vascular tissue and decaying then eventually causing death may well reign. Various earlier studies have linked the wilt disease in A. mangium in Sabah to a diverse group of microorganisms such as Fusarium, Lasiodiplodia, Verticillium, and more. In recent cases, there was a finding that attributed the fatal disease to fungi from the genus Ceratocystis sp. and more studies are expected with regard to the phenomenon.